Cost-effectiveness of single-use negative-pressure therapy compared with standard care for prevention of reconstruction failure in prepectoral breast reconstruction. Issue 2 (11th April 2021) - Murphy, J A; Myers, D; Trueman, P; Searle, R
Abstract: Background: Single-use negative-pressure wound therapy (sNPWT) has been reported to reduce the incidence of reconstruction failure in prepectoral breast reconstruction compared with standard surgical dressings. The aim of this economic evaluation was to investigate the cost-effectiveness of sNPWT compared with standard care for the prevention of reconstruction failure in prepectoral breast reconstruction in the UK. Method: A decision tree model was used to estimate the expected cost and effectiveness per patient. Effectiveness was measured both by the number of reconstruction failures avoided and the gain in quality-adjusted life-years (QALYs). The baseline incidence of reconstruction failure (8.6 per cent) was taken from a recently published study of 2655 mastectomies in the UK. The effectiveness of sNPWT used results from a clinical study comparing sNPWT with standard dressings. Previously published utility weights were applied. The cost of reconstruction failure was estimated from detailed resource data from patients with reconstruction failure, applying National Health Service reference costs. One-way, probabilistic, scenario and threshold analyses were conducted. Results: The undiscounted cost per patient associated with reconstruction failure was estimated to be £23 628 (£22 431 discounted). The use of sNPWT was associated with an expected cost saving of £1706 per patient, an expected increase in QALYs of 0.0187 and an expected 0.0834 reconstruction failures avoided. Cost-effectiveness acceptability analysis demonstrated that, at a threshold of £20 000 per QALY, 99.94 per cent of the simulations showed sNPWT to be more cost-effective than standard care. Conclusion: Among patients undergoing immediate prepectoral breast reconstruction, the use of sNPWT is more cost-effective than standard dressings. Abstract : The aim of this economic evaluation was to investigate the cost-effectiveness of single-use negative-pressure wound therapy (sNPWT) (PICO™) compared with standard care for the prevention of reconstruction failure in prepectoral breast reconstruction in the UK. Using a decision-analytical model, the use of sNPWT was associated with an expected cost saving of approximately €1880 per patient, an expected increase in quality-adjusted life-years of 0.0187, and an expected 0.0834 reconstruction failures avoided. This analysis suggests that use of sNPWT is more cost-effective than standard dressings for women undergoing immediate prepectoral breast reconstruction.